The Political Economy of Fuel Subsidy Removal: Governance and Sustainable Development in Nigeria - Gbadebo, Adedeji (Universitas Airlangga, 2025)
Abstract The removal of fuel subsidies in Nigeria has generated considerable debate regarding its implications for governance, economic stability, and public welfare. This study explores the governance mechanisms underpinning subsidy removal and assesses its economic and social consequences, drawing on data collected from 385 respondents in Bida, Niger State. A binary logit regression model was utilized to analyze the economic, social, political, and external variables influencing policy outcomes. The results indicate that, although the subsidy removal policy is intended to relieve fiscal burdens and promote economic efficiency, it has contributed to rising inflation and disproportionately impacted low-income households, thereby exacerbating social inequality. On the social front, the policy has incited significant public dissatisfaction, particularly due to escalating transportation and living expenses, while government-provided palliatives are widely perceived as insufficient. Politically, entrenched weaknesses in governance, a lack of transparency, and ongoing corruption have undermined public trust and complicated the policy’s legitimacy and acceptance. These findings highlight the centrality of governance in determining the effectiveness of economic reform policies. To mitigate adverse effects and enhance policy outcomes, the study recommends the implementation of targeted subsidies for vulnerable populations, increased investment in accessible public transportation infrastructure, and comprehensive institutional reforms to improve transparency and accountability in the allocation of subsidy savings. Ensuring that governance frameworks align with prevailing socio-economic realities is essential for achieving equitable and sustainable policy. Keywords: Fuel subsidy; governance; sustainable development; Nigeria; economic policy. Abstrak Penghapusan subsidi bahan bakar di Nigeria telah memicu perdebatan luas terkait dampaknya terhadap tata kelola pemerintahan, stabilitas ekonomi, dan kesejahteraan masyarakat. Studi ini mengeksplorasi mekanisme tata kelola yang mendasari kebijakan penghapusan subsidi serta menilai konsekuensi ekonomi dan sosialnya, berdasarkan data yang dikumpulkan dari 385 responden di Bida, Negara Bagian Niger. Model regresi logit biner digunakan untuk menganalisis variabel ekonomi, sosial, politik, dan eksternal yang memengaruhi hasil kebijakan. Hasil penelitian menunjukkan bahwa meskipun kebijakan penghapusan subsidi bertujuan untuk mengurangi beban fiskal dan mendorong efisiensi ekonomi, kebijakan tersebut justru menyebabkan peningkatan inflasi dan berdampak secara tidak proporsional terhadap rumah tangga berpendapatan rendah, sehingga memperparah ketimpangan sosial. Dari sisi sosial, kebijakan ini memicu ketidakpuasan publik yang signifikan, terutama akibat meningkatnya biaya transportasi dan biaya hidup, sementara bantuan sosial dari pemerintah dipandang tidak memadai. Secara politik, kelemahan dalam struktur tata kelola, kurangnya transparansi, dan korupsi yang terus berlanjut telah merusak kepercayaan publik serta memperumit legitimasi dan penerimaan kebijakan ini. Temuan ini menegaskan pentingnya peran sentral tata kelola dalam menentukan efektivitas kebijakan reformasi ekonomi. Untuk mengurangi dampak negatif dan meningkatkan hasil kebijakan, studi ini merekomendasikan pemberian subsidi yang ditargetkan bagi kelompok rentan, peningkatan investasi dalam infrastruktur transportasi publik yang terjangkau, serta reformasi kelembagaan secara menyeluruh guna meningkatkan transparansi dan akuntabilitas dalam pengelolaan dana hasil penghematan subsidi. Penyesuaian praktik tata kelola dengan realitas sosial-ekonomi yang ada merupakan hal yang krusial untuk mencapai reformasi kebijakan yang adil dan berkelanjutan. Kata kunci: Subsidi bahan bakar; tata kelola; pembangunan berkelanjutan; Nigeria; kebijakan ekonomi.